A relevância da experiência e seu papel formativo: acontecimento, criatividade e continuidade interativa - Hahn, Alexandre José (2018)
The research that gave rise to this job problematized the concept of experience, in order to show its relevance to school processes geared to integral human formation. We has investigate to what extent the concept of experience contributes to fostering life-oriented formation as an event of meaning and authentic living. Understanding that the opening of the subject to the experience is the best way to learn, we try to answer: What constitutes the formative role of a relevant experience in the school space? From the works of Jorge Larrosa (2016), Fayga Ostrower (2014) and John Dewey (1979), we carry out conceptual analysis work on the following categories: experience, creativity, interaction and continuity. The choice for these categories is justified by the direct relation with the realization and the human existence. The word experience is due to its aspect of connection with the human event and, as will be shown, there is no better word to describe what a relevant event in the subjects lives is. Experience is understood as what happens to us, that touches us, that can with a certain experiential (positive) impact create and foster senses of learning. Through experience, we discern what can make sense of human existence. In relation to creativity, your choice is given by the possibility of a practical orientation in an event. Taking this concept beyond its ordinary understandings, we will demonstrate that the act of creating is not an advanced activity of the human intellect, but something proper and possible to any human being. Creativity refers at the same time to a characteristic and a human need; we take it from this as a possibility of careful adaptation in living. On the continuity and interaction categories, it is demonstrated (with John Dewey) that there is an essential need for both to participate in an experience, so that the learning achieved in a relevant event generates intellectual growth and allows the next experiences to extract the maximum of its potential. In developing the dissertation, respectively, in the first two chapters, we make a concise and deep analysis of the term experience from the essays of Larrosa (2016) and the term creativity from Ostrower (2014). In the last chapter, we performed a kind of conceptual encounter between the theoretical perspectives of Dewey (1979) and the previously worked authors. We have shown that authors add up in a reasonable way, providing a clearer understanding of the orientation in the experience. We emphasize that action in experience will never really be oriented unless there is reflexive thinking about action. It is concluded that, through the cultivation of formative experiences in the school space, the subject can understand and transform his life in a more profound way than other formative actions. But in order to do so, it is necessary to ask what are the obstacles that prevent the experience from happening on the school floor. The research is of bibliographical character and is guided by investigative procedures appropriate to the philosophical hermeneutics.